Scientific Framework of Nahdlatul Ulama Education and Its Contribution to the Development of National Education - Sembodo Ardi Widodo (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The existence of Nahdlatul Ulama (NU) is inseparable from education. The birth of NU itself is also driven by the kyai who leaders in pesantren (Islamic boarding schools) are also. The growth of NU can be said to be in line with the growth and the development of pesantren educational institutions, madrasa educational institutions, and schools under the auspices of the Ma'arif institution. From year to year, the number of pesantren, madrasas, and schools managed by NU and also nahdliyin (communities who affiliate with NU organization) is increasing. This shows that NU, in terms of education, has made many scientific contributions to the Indonesian nation. This article is intended to explain the contribution of NU in education in Indonesia. This research is based on a literature study. The data were obtained from primary sources of documents related to the Nahdlatul Ulama organization and the thoughts of its main figures, data related to the Maarif educational institution (LP Maarif). The study focuses on the educational institutions under the auspices of NU, it’s a scientific and ideological framework that is used as the basis for thinking and behaving, as well as the development of NU educational institutions in the context of realizing the goals of national education